“LITERATURE AS THE EXPRESSION OF THE SELF” IN THE CONCEPTION OF MEDIEVAL VIETNAMESE LITERATURE - Van Vu, Dang (HNUE Journal of Science: Journal of Social Sciences, 2026)
The role and position of literature in human life has always been a matter of concern throughout history. To define this is also to define the very existence of literature in society. While today much attention is paid to the notion of “literature as a form of human inquiry,” earlier thinkers extensively discussed the idea of “literature as an expression of the self.” This issue has attracted attention since very early times, both in the East and the West. In Vietnam, due to specific cultural and historical conditions as well as socio-economic circumstances, medieval writers regarded literature first and foremost as the most fundamental means of expressing their human identity. Such expression, on the one hand, revealed their personhood, and on the other, contributed to the formation of individual literary style. More broadly, the notion of “literature as man” also implies literature for humanity, serving to humanize function. Employing socio-cultural approaches, comparative methods, and analytical and synthetic methods, this article clarifies how the concept of “literature as man” operates in the medieval period, viewed in reference to modern perspectives.